Construct validity and reliability of the Full Outline of UnResponsiveness (FOUR) score in spontaneous subarachnoid haemorrhage caused by aneurysm rupture. Issue 21 (9th August 2019) - Oh, HyunSoo; Shin, SeonYoung; Kim, SooHyun; Seo, WhaSook
Abstract: Aims and objectives: This study aimed at examining the construct validity and reliability of the Full Outline of UnResponsiveness score in patients with spontaneous subarachnoid haemorrhage caused by aneurysm rupture. Background: The Full Outline of UnResponsiveness score is known to be a valid and reliable consciousness assessment tool and provides comprehensive information not given by the Glasgow Coma Scale. However, the validity and reliability of this tool have not been tested in patients with spontaneous subarachnoid haemorrhage. Design: A nonexperimental, descriptive, correlational study design was adopted. Methods: The STROBE statement was used for reporting this study. The study participants were 72 patients with spontaneous subarachnoid haemorrhage caused by aneurysm rupture, admitted to an intensive care unit in a university hospital between August 2016–July 2017. Data on demographic characteristics, Hunt–Hess clinical stage scores, Fisher CT stage scores, disease‐related characteristics, Full Outline of UnResponsiveness scores and 1‐month Glasgow Outcome Scale scores were subjected to analysis. Results: Full Outline of UnResponsiveness scores were found to have significant correlations with scores on Hunt–Hess clinical or Fisher CT stage tool and adequately predict 1‐month recovery. This tool also exhibited excellent inter‐rater agreement and internal consistency. Conclusions: The Full Outline of UnResponsiveness score is valid and reliable for consciousness evaluation in spontaneous subarachnoid haemorrhage. It has been believed that use of this tool may help prevent negative consequences arising from impaired consciousness and improve the outcomes of patients with spontaneous aneurysmatic subarachnoid haemorrhage. Relevance to clinical practice: The Full Outline of UnResponsiveness score is a consciousness assessment tool that provides more neurological detail because it includes consideration of brainstem reflexes, visual tracking, breathing patterns and respiratory drive, and can be applied in cases of spontaneous subarachnoid haemorrhage and other types of brain injury, especially in patients with severe consciousness impairment.